Effects of high-intensity interval training on the anthropometric profile of overweight and obese adult women (2016)
Introduction: Sedentary lifestyle, overweight and obesity in adult women have high prevalence.Objective: To determine the effects of a high intensity interval training program on the anthropometric profile of overweight or obese women.Materials and methods: 24 adult women, including 16 with overweight and 8 with obesity, between 26 and 49 years of age, were selected to participate in a two month high intensity training program (three sessions per week). Weight, height, BMI, muscle mass percentage, and fat mass and visceral fat percentages were assessed.Results: The adherent group (≥75% assistance) was composed by 16 participants, while the non-adherent group (assistance 75%), by 8 participants. No significant differences were found among both groups previous to and after the intervention (p≥0.05).The non-adherent group did not show any significant change, while the adherent group improved (p0.05) their variables of weight (p0.001), BMI (p0.001), fat mass percentage (p0.001), muscle mass percentage (p0.001) and visceral fat percentage (p=0.020) after the intervention.Conclusions: The training program improved the anthropometric profile of the participants without requiring specialized equipment or involving high costs, thus, this procedure is recommended for the treatment of malnutrition by excess in this type of population.